MODIFIKASI RANCANGAN BRACKET CALIPER MENGGUNAKAN MESIN CNC DENGAN METODE PERANCANGAN VDI 2221 - Muh. Nurul Haq Amaluddin; Ridwan Jamaludin (Unit Penelitian, dan Pengabdian Masyarakat (UPPM) Politeknik ATI Makassar, 2023)
Caliper is a part of a motorcycle, especially in the braking system, which functions as a brake pad suppressor to press the disc brake so that the motorcycle can stop or slow down according to its needs. Currently, the replacement of motorcycle calipers, especially on motorcycles that have a cubication of 250cc, is becoming a necessity among 250cc motorcycle owners. Replacing a motorcycle caliper requires a supporting part as a holder as well as a caliper holder or commonly called a caliper bracket. The caliper bracket is needed because the caliper to be installed has a larger shape and size when compared to the standard motorcycle caliper, so a caliper bracket that fits its size is needed. The bracket caliper products that are currently circulating have several shortcomings, such as the inaccuracy of the bracket, the difficulty of getting bracket products, and the ever-changing price. Therefore, this study aims to design a bracket caliper independently using CNC machine and accompanied by modification of the variable size using the VDI 2221 method. The modified component points are part of the caliper bracket. The characteristics of this method have 4 phases, namely, the description of the design task of the bracket caliper, the design of the design concept, the design of the product form, and the description of the details